2x+23=2/9x

Simple and best practice solution for 2x+23=2/9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+23=2/9x equation:



2x+23=2/9x
We move all terms to the left:
2x+23-(2/9x)=0
Domain of the equation: 9x)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
2x-(+2/9x)+23=0
We get rid of parentheses
2x-2/9x+23=0
We multiply all the terms by the denominator
2x*9x+23*9x-2=0
Wy multiply elements
18x^2+207x-2=0
a = 18; b = 207; c = -2;
Δ = b2-4ac
Δ = 2072-4·18·(-2)
Δ = 42993
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{42993}=\sqrt{9*4777}=\sqrt{9}*\sqrt{4777}=3\sqrt{4777}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(207)-3\sqrt{4777}}{2*18}=\frac{-207-3\sqrt{4777}}{36} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(207)+3\sqrt{4777}}{2*18}=\frac{-207+3\sqrt{4777}}{36} $

See similar equations:

| -18-(x/4)=-20 | | -5x+103=63 | | 4x-3+9x=3x-9 | | 3x-71=86 | | x-8+6x=-43 | | -3x+37=16 | | -4x+51=43 | | 2y+1=3y | | x^2=40–18x | | 1,5x+7=2,5 | | 3/4t=13 | | -18=m+9 | | x2=40–18x | | -1/2t=-12 | | -19(k+3)=-15k-4k | | -4/3t=2 | | y/7+1=3 | | -3n+5-7=-25 | | -1/4x+5/8=-9/4x | | 7.5=l*25 | | 96t+245=53 | | -1/8x=-5x+5/8 | | 5y-2^=15 | | 6^(5x-17)=218 | | -17=m+8 | | 6(x-5)=5(x-5 | | 7x-13=+8 | | x^2=40–18x | | 8(7x+5)=-5(4x-8) | | 7)d-2)=5(d+2) | | 2w+2(w+44/3)=1371/2 | | 2x=7=2x=19 |

Equations solver categories